Peiminine Suppresses RANKL-Induced Osteoclastogenesis by Inhibiting the NFATc1, ERK, and NF-κB Signaling Pathways - Zhu, Mengbo; Xu, Wenbin; Jiang, Jiuzhou; Wang, Yining; Guo, Yanjing; Yang, Ruijia; Chang, Yaqiong; Zhao, Bin; Wang, Zhenyu; Zhang, Jianfeng; Wang, Te; Shangguan, Liqin; et al. (Frontiers in Endocrinology, 2021)
Osteoclasts (OCs) play an important role in osteoporosis, a disease that is mainly characterized by bone loss. In our research, we aimed to identify novel approach for regulating osteoclastogenesis and thereby treating osteoporosis. Previous studies have set a precedent for screening traditional Chinese herbal extracts for effective inhibitors. Peiminine is an alkaloid extracted from the bulb of Fritillaria thunbergii Miq that reportedly has anticancer and anti-inflammatory effects. Thus, the potential inhibitory effect of peiminine on OC differentiation was investigated via a series of experiments. According to the results, peiminine downregulated the levels of specific genes and proteins in vitro and consequently suppressed OC differentiation and function. Based on these findings, we further investigated the underlying molecular mechanisms and identified the NF-κB and ERK1/2 signaling pathways as potential targets of peiminine. In vivo, peiminine alleviated bone loss in an ovariectomized mouse model.